The Optimum Water Management on Tidal Irrigation Land Telang I, South Sumatera - Pande Munthe; Nora H Pandjaitan (Jurnal Keteknikan Pertanian, 1998)
The increasing of food demand and maintaning the national food self supporting program have become the goverment concern. On the other side farm land convertion (especially in Java and Bali) into non-farm land has increased. So, as one of the solution, the goverment has opened many new farm lands outside Java. Most of them are tidal land. Tidal lands need an occurate contruction and water management system. The aim of the study is to determine the water management system for tidal irrigation land (on farming level) by controling water surface according to the cropping pattern. The location of study is Telang I tidal irrigation area, Kabupaten MusiBanyuasin, South Sumatera.